Within-day amino acid intakes and nitrogen balance in male collegiate swimmers during the general preparation phase - Matsuda, T.; Kato, H.; Suzuki, H.; Mizugaki, A.; Ezak, T.; Ogita, F. (Nutrients, 2018)
A higher protein intake is recommended for athletes compared to healthy non-exercising individuals. Additionally, the distribution and quality (i.e., leucine content) of the proteins consumed throughout the day should be optimized. This study aimed to determine the nitrogen balance and distribution of protein and amino acid intakes in competitive swimmers during the general preparation phase. Thirteen swimmers (age: 19.7 ± 1.0 years; VO2max: 63.9 ± 3.7 mL/kg·min, mean ± standard deviation) participated in a five-day experimental training period. Nutrient intakes were assessed using dietary records. Nitrogen balance was calculated from the daily protein intake and urinary nitrogen excretion. The intake amounts of amino acids and protein at seven eating occasions were determined. The average and population-safe intakes for zero nitrogen balance were estimated at 1.43 and 1.92 g/kg·day, respectively. The intake amounts of protein and leucine at breakfast, lunch, and dinner satisfied current guidelines for the maximization of muscle protein synthesis, but not in the other four occasions. The population-safe protein intake level in competitive swimmers was in the upper range (i.e., 1.2-2.0 g/kg·day) of the current recommendations for athletes. The protein intake distribution and quality throughout the day may be suboptimal for the maximization of the skeletal muscle adaptive response to training.